Prediction of normal values for central apnea-hypopnea index at different ages and altitudes above sea level in healthy children (2021)
Background: There is a critical need for studies aimed to help clinicians to establish the normal/expected central apnea-hypopnea index (CAHI) at altitudes above sea level and ages other than those reported in the current available studies. The aim of the present study was to develop predictive models useful for determining the normal/expected CAHI in children of different ages born and living at various altitudes above sea level. Methods: A systematic review of the literature was performed in order to identify all available studies that reported on CAHI values measured in healthy children of different ages and living at various levels above sea level. In order to identify factors independently associated with CAHI values, they were fit to multiple linear and quantile regression models. Results: A total of 16 studies that reported on CAHI values measured in healthy children living at various levels above sea level were included in the analyses. Out of the 16 studies, 12 (75%) were conducted in low-altitude cities, 1 (6.2%) was conducted in a medium-altitude city, 2 (12.5%) in high-altitude cities, and 1 (6.2%) in both low- and high-altitude cities. Age and altitude above sea level are independent predictors of CAHI values in the linear regression analysis and in the quantile regression at the ninetieth percentile. Conclusions: The best-fitting prediction equations were obtained with linear regression and quantile regression at the ninetieth percentile analyses, and either of the two models could be used to predict the normal/expected CAHI values in healthy children